Educational Qualifications Of Du’at: An Analysis Of Muhammad Al-Ghazali (1917-1996) Thought - Surizkika, Aldi (Mustaneer : Journal of Islamic Thought and Civilization, 2025)
This article examines the da'wah thought of Muḥammad al-Ghazālī (1917–1996) by emphasizing the importance of integration between the classical Islamic scientific tradition and the approach of modern science in shaping the intellectual competence of da'ī (preachers). Al-Ghazālī criticized the religious education system that tended to be textualistic and narrow in scope, and proposed a multidisciplinary, rational, and progressive model of da'wah. The main purpose of this paper is to evaluate the epistemological relevance of al-Ghazālī's ideas in the context of contemporary da'wah challenges. With a qualitative approach based on library research, data was collected from al-Ghazālī's works and relevant secondary literature. The results of the study show that al-Ghazālī places intellectual formation as the main axis of the success of da'wah, by demanding that the da'ī master not only Islamic texts, but also philosophy, sociology, psychology, economics, natural sciences, and the history of human civilization. The main contribution of this article lies in the articulation of an integrative da'wah model that rejects the dichotomy between religion and science, as well as suggesting a redefinition of da'ī competence in a global landscape. The practical implications of this thinking lead to the importance of reforming the da'wah education curriculum that is adaptive to the complexity of the times.